Responding to a resurgent Russia Russian policy and responses from the European Union and the United States - Govella, Kristi (Springer New York, 2012)
In this volume, a set of issue and country experts tackle the questions surrounding the challenges of a resurgent Russia for the world order as well as for relations between the European Union and the United States.  Following a brief introduction laying out the circumstances of Russia's rise, the book proceeds in three sections. In the first, Russian scholars tackle the topic of how a newly resurgent Russia sees the world. The second section examines Russia's role in the contemporary global political economy in terms of trade and financial flows and nuclear energy. The third section looks at American and European responses to Russia, and the conclusion draws together the findings from each of the chapters and presents some broad propositions regarding Russia's rise and the challenges that it presents for the US, EU and the international order in the years to come.  The implications of this collection are very broad and far-reaching, with ramifications for each of the players involved as well as for the development and refinement of general international relations theories concerning global conflict and cooperation, making the book relevant for both policy-makers and scholars of international relations, Russian studies, and international political economy.